Peran Agama dan Pendidikan dalam Multikulturalisme Masyarakat Indonesia - Setiono, Yusup Agus (Bestari, 2022)
Multiculturalism is the realization that several different cultures can live in the same environment and mutually benefit. Indonesia is a very diverse nation, it cannot be denied. Indonesia's diversity is not only reflected in the number of islands united under the rule of one country, but also in the diversity of skin color, language, ethnicity, religion and culture. From a sociological perspective, religion is understood as a belief system attached to certain patterns of social behavior. Religion influences human experience both as individuals and as groups. Therefore, the behavior of individuals or groups is related to the belief system of the religious teachings they adhere to. Different religious views can lead to bigotry and isolation from other views in society. Then religion can cause internal and external conflicts which in the end can harm society itself.